LITERATURE REVIEW: USE OF ESSENTIAL OIL AROMATHERAPY TOWARDS PAIN REDUCTION IN CANCER PATIENTS - Lopulalan, Syaneti; Antia, Antia; Sukarno, Anita; Asmirajanti, Mira (Journal of Islamic Nursing, 2021)
Pain is one of the most common symptoms experienced by cancer patients, and as much as 68% of the causes of pain are experienced by cancer patients (primary tumors). Patients with pain should receive the treatment that can provide the greatest benefit in pain management. For this reason, this research was conducted with the aim of; The purpose of this study was to find out the effect of the use of aromatherapy inhalation of essential oils on reducing pain in cancer patients. The method used in this study is to use "Literature review" with the amount of literature to be studied, namely 14 research titles in the form of journals/articles that are following the topic of the problem in this study. Amount The total respondents who were put together from the 14 studies were 1,108 patients with pain disorders/complaints. 34.65% of them are male, 35.19% are female, are in the age limit of 1-60 years; 1-15 years = 37.72%., 16-26 years = 18.05%., 27-35 years = 5.65%., and 36-60 years old = 17.14%. The results of the action of giving aromatherapy carried out in the 14 studies showed that there was an effect obtained from the use of essential oil aromatherapy through inhalation techniques, where there was a change in the pain scale before and after the action of giving aromatherapy.